Implementasi berfikir irfani untuk kualitas diri yang lebih baik pada kehidupan digital - Anatasia, Nadita Leli; Kusuma, Yunani; -, Faisol (Maliki Interdisciplinary Journal, 2025)
In theosophy there are three categories of thinking methods used until now, namely bayani, burhani and irfani thinking methods. This study discusses the irfani method of thinking which according to Muhammad Abid al-Jabri is a way of thinking based on spiritual experience and intuition. Epistimology is considered important because it can create quality morals in society. This research applies qualitative research methods that are strengthened by relevant literature sources. The result of this study is that irfani thinking acts as a controller of human behavior in this digital era such as increasing self-awareness, strengthening digital ethics and digital responsibility so that the quality of life will improve spiritually in this technological era.